Belas Kasih Allah dalam Penerimaan Komuni Suci Bagi Orang dengan Retardasi Mental - Chosmas Christian Timur (Sekolah Tinggi Filsafat Seminari Pineleng, 2020)
People with mental retardation have limitations in intellectual and adaptive functioning. Intellectual functioning refers to general mental capacity such as learning, reasoning, problem solving, and so forth. Therefore, a person with mental retardation has limited understanding of the Body and Blood of Christ. Though it must be owned by the recipient of Holy Communion. This research aims to find pastoral solutions for people with mental retardation in the reception of Holy Communion. They have to obtain the divine grace of Christ through the sacraments if it is possible. This essay proposes a theological and pastoral discussion about this theme.